Vliv chemismu vody a charakteru litorálu na společenstva vodního hmyzu horských nádrží a jezer - Sivý, Štěpán (Jihočeská univerzita, 2018)
This thesis focuses on the composition and diversity of aquatic invertebrate assemblages of 23 standing water sites in the Czech Republic (Šumava Mts., Krušné Mts., Jizerské Mts.) and Germany (Bavarian Forest). The sites included mountain lakes, ponds and reservoirs with different littoral zone characteristices and water chemistry. Study sites were selected with respect to former acidification of mountain regions. Environmental factors shaping littoral invertebrate assemblages composition were investigated.
The effect of water chemistry and littoral structure on aquatic insects communities of mountain reservoirs and lakes